The effect of adding shrimp shell meal in feed as an additional mineral source in aquaculture vannamei shrimp (Litopenaeus vannamei) in freshwater - Scabra, Andre Rachmat; Murtadha, Hasan Murtadha; Diniariwisan, Damai Diniariwisan (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2025)
Vannamei shrimp have euryhaline properties, which are biota that can survive in a wide salinity, this ability opens up great opportunities for farmers to develop vannamei shrimp farming in freshwater. However, the problem faced by vannamei shrimp farmers in freshwater media is that their growth is less than optimal due to mineral deficiencies. The need for minerals in aquatic biota depends on the type, reproduction, environment and the ability of biota to absorb minerals from the environment. Aquatic biota has the ability to absorb minerals in the water but not optimally, so it is very important to add mineral content in the feed, one of which is calcium. Calcium can be obtained from shrimp shells or shells which can be used as an additional mineral source that can be applied in commercial shrimp feed because it contains 25-40% protein and 45-50% calcium carbonate. This study aims to determine the effect of the addition of shrimp shell flour in feed on the growth and survival of freshwater vannamei shrimp. The treatments in this study were P1 without the addition of shrimp shell meal, P2 with the addition of 1% shrimp shell meal, P3 with the addition of 2% shrimp shell meal, P4 with the addition of 3% shrimp shell meal and P5 with the addition of 4% shrimp shell meal. Where the best treatment in this study is in the P5 (4%) treatment with the addition of shrimp skin flour. Treatment P5 (4%) has a specific weight of 3.32%, specific length of 3.32%, feed conversion ratio of 1.13 and survival rate of 35%.